PENERAPAN SOPEP DALAM PENANGANAN TUMPAHAN MINYAK PADA MV. DK02 - Yandri Aditya; Rizal Rochmansyah; Arya Widiatmaja; Ahmad Gifari M (STKIP Subang, 2026)
SOPEP is a box that is usually red or yellow and has the words SOPEP written on it and contains tools used to prevent oil spills, such as rags, sand, sawdust, oil spill dispersant (OSD), brooms, and buckets. SOPEP (Shipboard Oil Pollution Emergency Plan) is a plan for handling oil spills into the sea that every ship must have. MARPOL 73/78 Annex I, requires that all ships with GT 400 and above must (for tankers starting from GT 150 and above) be equipped with SOPEP equipment following the instructions given by IMO and MEPC (Marine Environmental Protection Committee). Sailing practice is carried out at MV.DK02. The method used in this research is the descriptive qualitative method. That is a research method that utilizes qualitative data and is described descriptively. The results of this study indicate that the constraints experienced by the kru when implementing SOPEP on ships were the kru's lack of knowledge about SOPEP and the tools in it, who should already be familiar with SOPEP tools and their uses.